Sobrevivência de enxertos de Eucalyptus com metodologia adaptada - Moraes, Cristiano Bueno de [UNESP]; Silva, Paulo Henrique Müller da; Abilio, Fernanda Maria; Pieroni, Gustavo Bloife; Gonçalves, Antônio Natal; Mori, Edson Seizo [UNESP] (My University, 2013)
One of the important techniques to assist a tree improvement program is the grafting, which is used for the propagation of selected trees. The objective of this study was to evaluate the survival rate using a modified method of lateral grafting on Eucalyptus dunnii, Eucalyptus urophylla and a hybrid of Eucalyptus urophylla x Eucalyptus grandis. The work was conducted by the research teams of Eucatex and Palmasola companies, in September of 2011, and 589 grafts were made. The survival rate of the grafts was evaluated 180 days after grafting. Survival grafts rates were: 74% for E. dunnii, 55% for E. urophylla and 62% for the hybrid E. urophylla x E. grandis. These survival rates were higher than those currently obtained by the conventional method of eucalypt grafting. Thus, the method seems promising to assist in forest tree improvement programs, but further studies are still necessary to refine this grafting approach.

Dentre as técnicas importantes que auxiliam no programa de melhoramento florestal está o processo de enxertia, que é utilizada para propagação das matrizes superiores selecionadas. O objetivo deste trabalho foi verificar a taxa de sobrevivência de E.dunnii, E. urophylla e o híbrido de E. urophylla x E. grandis com a utilização da metodologia modificada de enxertia por garfagem lateral. O trabalho foi conduzido pelas equipes de pesquisas das empresas Eucatex e Palmasola em setembro de 2011, com a realização de 589 enxertos. A taxa de sobrevivência (“pegamento”) dos enxertos foi avaliada aos 180 dias após a confecção. Foi constatado que o método usado resultou em pegamento de 74% para E. dunnii, 55% para E. urophylla e 62 % para o híbrido E. urophylla x E. grandis. Esses índices foram superiores aos obtidos atualmente pelos métodos tradicionais de enxertia realizados em Eucalyptus. O método se mostrou promissor para atender as necessidades de programas de melhoramento florestal, mas ainda são necessários estudos para o seu refinamento.
Grafts survival of Eucalyptus with adapted methodology
Keywords: Propagation; Lgrafting; Tree improvement; Propagação; Garfagem lateral; Melhoramento florestal